Exploration and implementation of a smart tourism destination with the 6As framework & TOPSIS (case study: Wakatobi, Indonesia) - Agustan; Usman Rianse; Endro Sukotjo; Arman Faslih (Przegląd Naukowy Inżynieria i Kształtowanie Środowiska, 2024)
Wakatobi represents huge potential for smart tourism due to the rich natural, cultural, and man-made resources available. The objective of the research is to identify and analyze the tourism potential of Wakatobi by using the 6As framework (attractions, accessibility, amenities, available packages, activities, and ancillary services) and applying the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to rank the potential tourist destinations. Field observations, collection of secondary data, and stakeholder interviews were conducted to arrive at comprehensive data on the tourism assets of the islands. The result of the exploration successfully recorded 160 attractions in the form of geographical destinations and activities with a variety of visitor facilities around them, which were measured using the 6As framework. The TOPSIS results indicated that Wangi-Wangi Island had the highest rank (0.87) in overall tourism potential compared to the others due to better infrastructural conditions, diverse attractions, and better facilities. Furthermore, it revealed major discrepancies among the islands, thus requiring focused improvements related to accessibility and services for less developed areas like Kaledupa (0.28), South Kaledupa (0.26), and Tomia (0.25). This study provides the basic insights for policymakers and stakeholders to invest in the right areas to ensure balanced and inclusive growth, increasing the tourism attractiveness of Wakatobi with a focus on sustainability and community involvement.